2023
DOI: 10.3390/plants12122356
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Mechanism of Salt Tolerance in Maize: A Classic Field That Needs New Efforts

Jiawei Li,
Qinglin Zhu,
Fuchao Jiao
et al.

Abstract: Maize is the most important cereal crop globally. However, in recent years, maize production faced numerous challenges from environmental factors due to the changing climate. Salt stress is among the major environmental factors that negatively impact crop productivity worldwide. To cope with salt stress, plants developed various strategies, such as producing osmolytes, increasing antioxidant enzyme activity, maintaining reactive oxygen species homeostasis, and regulating ion transport. This review provides an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 107 publications
(135 reference statements)
0
0
0
Order By: Relevance
“…Setubal et al [10] observed that nitrogen fertilization is inefficient for seed yield in soybeans under drought. Finally, Li et al [11] revised different mechanisms associated with maize salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Setubal et al [10] observed that nitrogen fertilization is inefficient for seed yield in soybeans under drought. Finally, Li et al [11] revised different mechanisms associated with maize salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The articles published in this SI covered the identification and characterization of transcription factors associated with stress resistance [1][2][3], beneficial endophytic/plant interaction [4,5], and molecular mechanisms involved in crops and fruit plants to stress tolerance [6][7][8][9][10][11].…”
Section: Overview Of Simentioning
confidence: 99%
See 1 more Smart Citation